Stark reality: It's 'worse', not 'bad' - Abd Razak, Dzulkifli (2007)
A SELECT group of heads representing leading institutions of higher learning in the AsiaPacific region was invited to the United Nations University's Institute of Advanced Studies last week to deliberate and act on the issues of sustainable development. The focus of the meeting was on the roles of postgraduate sustainable development education and research. It sought to initiate collective action through the formation of a network to urgently deal with the pressing issue.